2019
DOI: 10.1186/s12966-019-0816-3
|View full text |Cite
|
Sign up to set email alerts
|

Joint physical-activity/screen-time trajectories during early childhood: socio-demographic predictors and consequences on health-related quality-of-life and socio-emotional outcomes

Abstract: Background Understanding the early roots of physical activity and sedentary behaviors is critical to developing intervention programs that promote healthy lifestyle habits in infants and children. There is, however, no evidence on how these behaviors cluster and develop together during early childhood. The aim of this study was to identify single and joint longitudinal trajectories in physical activity and screen time amongst children aged 0 to 9 years, their social-demographic predictors and thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
33
0
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 47 publications
5
33
0
1
Order By: Relevance
“…These associations were statistically signi cant over and above children's further health behaviors -physical activity and sleep, as well as income and other demographics. Our results substantiate the ndings from previous research that have shown a negative link between screen time and physical [50], social-emotional [51] and mental health [9] outcomes among preschool-aged children.…”
Section: Discussionsupporting
confidence: 91%
“…These associations were statistically signi cant over and above children's further health behaviors -physical activity and sleep, as well as income and other demographics. Our results substantiate the ndings from previous research that have shown a negative link between screen time and physical [50], social-emotional [51] and mental health [9] outcomes among preschool-aged children.…”
Section: Discussionsupporting
confidence: 91%
“…A list of items coded as screen time is provided in Additional file 1: Table S1. Time-use diaries have been successfully used in previous studies investigating health behaviours in children [1620].…”
Section: Methodsmentioning
confidence: 99%
“…It is clear from the above mentioned, that in order to establish the importance of physical activity in everyone's consciousness, the corresponding habits for health and quality of life should be instilled from an early age (Sallis & Patrick, 1994;Telama, Yang, Laakso & Vilkari, 1997;Del Pozo-Cruz et al, 2019). It is for this reason that PE and the influence of the PE teacher play a key role in school life, not only in cultivating motor and cognitive skills, but also in improving the quality of students' life in the present as well as in the long term (Sallis & McKenzie, 1991;Wright, Patterson, & Cardinal, 2000).…”
Section: Introductionmentioning
confidence: 99%